Revitalisasi Pemandian Air Panas Sumberjo sebagai Desa Wisata Wellness dengan Konsep Neo-Vernakular dan Branding Partisipatif - Dhiah Agustina Qahar; Ine Destiana Rahmandani; Bhimas Bukin; Malihatus Sa’diyah; Emil Sulistya Ningrum (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to create a conceptual design for the revitalization of the Kali Panas Sumberjo hot spring as a sustainable tourism destination in Sumberjo Village, Widang District, Tuban Regency, using a descriptive qualitative approach through Community Service activities. The Asset-Based Community Development (ABCD) approach is used to map the potential of natural resources, MSMEs, and the social dynamics of the local community. The research results indicate that the revitalization of Kali Panas Sumberjo can focus on the concept of Wellness Tourism, which integrates health, relaxation, and tranquility through the use of mineral-rich hot spring water. A Neo-Vernacular architectural concept is proposed, incorporating traditional Joglo elements and modern materials for efficiency, thereby reflecting the local cultural identity. A branding strategy with the tagline “Joglo Happiness Hydrotherapy” is developed to strengthen digital promotion and tourist appeal. Additionally, the empowerment of local MSMEs as providers of culinary services, crafts, and accommodations serves as a supporting element for economic and social dimensions. This integrated approach is not only intended to enhance tourism potential but also to ensure sustainable economic and social benefits for the village community through a replicable development model.